Dimensions of aesthetic encounters : perception, interpretation, and the signs of art - Innis, Robert E. (State University of New York Press, 2022)
A novel fusing of multiple approaches and range of examples exploring the dimensions, objects, and import of aesthetic encounters.
Description based upon print version of record.
Keywords: Dewey, John, -- 1859-1952.; Peirce, Charles S. -- (Charles Sanders), -- 1839-1914.; Dewey, John, -- 1859-1952; Peirce, Charles S. -- (Charles Sanders), -- 1839-1914; Aesthetics.; Art -- Philosophy.; Art -- Philosophie.; PHILOSOPHY / Aesthetics.; Aesthetics; Art -- Philosophy